PERANCANGAN DAN IMPLEMENTASI WEBSITE LAYANAN AKADEMIK DI SMA NEGERI 07 BANDAR LAMPUNG - Yohana Tri Utami; Riki Sofyan; Rd. Irwan Adi Pribadi (Inovasi Pembangunan : Jurnal Kelitbangan, 2021)
This research focuses on creating a website for academic services at SMA Negeri 07 Bandar Lampung. It aims to design and realize a web-based academic information system for SMA Negeri 07 Bandar Lampung using the Laravel Framework with the PHP programming language and MariaDB as the database server. In designing an academic information system at SMA Negeri 07 Bandar Lampung that uses the Waterfall method, it is divided into several user accesses, namely administration (admin), teachers and homeroom teachers, each of which has access to different features. With the existence of the SMA Negeri 07 Bandar Lampung website, the school has an alternative media for providing information, making it easier to manage and search for academic data. System testing that has been carried out results in an assessment for satisfaction at an average rating of 99.75% with the "Very Good" category.